2014
DOI: 10.1111/bjh.13023
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction accurately predicts clinical outcome in chronic lymphocytic leukaemia, even in patients with early stage disease

Abstract: SummaryDefining the prognosis of individual cancer sufferers remains a significant clinical challenge. Here we assessed the ability of high-resolution single telomere length analysis (STELA), combined with an experimentally derived definition of telomere dysfunction, to predict the clinical outcome of patients with chronic lymphocytic leukaemia (CLL). We defined the upper telomere length threshold at which telomere fusions occur and then used the mean of the telomere 'fusogenic' range as a prognostic tool. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 33 publications
4
89
0
1
Order By: Relevance
“…In particular, mutant patient cells contained telomeric STELA products <2.3 kb, which have been correlated with telomere dysfunction and fusion (Lin et al 2014). The finding that telomerase can immortalize the POT1 CP cells and diminishes the presence of the extremely short telomeres argues in favor of the shortened telomeres causing the observed proliferation defect.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, mutant patient cells contained telomeric STELA products <2.3 kb, which have been correlated with telomere dysfunction and fusion (Lin et al 2014). The finding that telomerase can immortalize the POT1 CP cells and diminishes the presence of the extremely short telomeres argues in favor of the shortened telomeres causing the observed proliferation defect.…”
Section: Discussionmentioning
confidence: 94%
“…We used haplotype analysis to confirm the involvement solely of the shorter MRC5 HPVE6E7 XpYp allele (Baird et al 2003) in these sequenced fusions (Supplemental Fig. 1B), consolidating demonstrations of the length-dependent threshold for telomere fusion to occur (Capper et al 2007;Lin et al 2014). We performed manual curation and sequence verification of all telomere linkages exceeding mapping quality (Li 2014) and BLAST alignment (Altschul et al 1990) score thresholds defined using training data sets (described in the Supplemental Methods).…”
Section: High Resolution Mapping Of Inter-and Intra-chromosomal Recommentioning
confidence: 88%
“…Most of our patients (86 %) were studied at an early stage of the disease. Different authors [22,30,31] found evidences of telomeric damage in early stage patients suggesting that short telomeres could be a possible marker for clinical progression. In addition, Ricca et al [11] referred preliminary results indicating that TL is not always stable over time in CLL, and suggesting that TL is influenced by the natural history of the disease.…”
Section: Discussionmentioning
confidence: 99%